Cultura tributaria de los microempresarios y la evasión fiscal - Santacruz Jiménez, Angie Cristina (2023)
The present work of degree called Tax culture of microentrepreneurs and tax evasion, addresses information regarding the factors of the tax culture of microentrepreneurs marketers of clothing, shoes and various items, which could affect the evasion of their tax obligations, which is why the objective was to analyze the influence of the factors of the tax culture in the microentrepreneurs of the bay "Tierra Dulce" in relation to tax evasion. For the collection of information, research techniques were used: interviews, surveys, observation sheets, Documentary analysis of the tax process of three microentrepreneurs, where a review was carried out to detect possible shortcomings and suggest corrective actions. Among the main conclusions, it was obtained that the current situation of the tax culture of microentrepreneurs is scarce, due to the high level of ignorance of the laws and the tax process. Through the review and analysis of the tax process, the methods detected with the greatest shortcomings were: issuance of vouchers, registration of transactions of purchases and sales and tax returns, the appropriate suggestions were made.